COMPARISON OF MICROBIOLOGICAL ANALYSIS METHODS IN THE SOFT DRINK INDUSTRY - Maria Rosiki Conti, Francisca (Journal of Interdisciplinary Debates, 2023)
Water is essential for living beings. It is also one of the main means of transporting contaminants such as pathogenic bacteria. Therefore, water quality must meet basic requirements so that it can be consumed by the population and for use in industries. The objective of this work was to carry out a comparison of two analysis methods (Petrifilm® and Chromogenic Substrate) of water in the beverage industry, contributing to the validation study of the Petrifilm® method for analysis of process water for coliform microorganisms. Currently, only the Chromogenic Substrate method is validated by the Standard Methods for the Examination of Water and Wastewater. The study was carried out in a soda fountain in the city of Jundiaí-SP. Tests were performed over a period of 6 months, weekly (for process water) and monthly (for line swab). Specific points were chosen for sample collection according to the internal procedure. The obtained results demonstrated that the Petrifilm® method was not efficient to demonstrate the presence of coliforms and comparison with the chromogenic substrate.